Expiry of veterinary medicines in supply outlets in Central Uganda: prevalence, management and associated factors - Stevens Kisaka; Frank K. Tumwebaze (Journal of Pharmaceutical Policy and Practice, 2023)
Abstract Background Animal diseases are a danger to livestock, businesses, and public health. This is why the public and private sectors in Africa have invested immensely in the manufacture and distribution of veterinary drugs. However, veterinary drug supply chain actors still suffer losses as a result of expiration. Besides, the way expired products are managed might pose risks to human, animal, and environmental health. This study investigated the prevalence, management of, and factors associated with the expiry of veterinary medicines in supply outlets in Central Uganda. Methods A cross-sectional study was conducted among owners and caretakers of veterinary drug supply outlets. Data were collected using self-administered, semi-structured questionnaires. The level of expiry was computed as “acceptable” (for levels reported as ≤ 5%) and “unacceptable” (for levels reported as ˃5%). Logistic regression was used to assess associations between the level of drug expiry and predictor variables. Results A total of 168 owners/caretakers of veterinary drug supply outlets were included in this study. The majority (148/168, 88.1%) of respondents reported having experienced expiries in their outlets. Unacceptable levels of expiry were reported in 38/168 (22.6%) of the outlets. Retail outlets accounted for the majority (34/38, 89.5%) of the unacceptable levels. Powdered drugs accounted for most expiries (106/148, 71.6%). Most expiries were for drugs supplied to outlets on credit (58/124, 46.8%) and those used to treat rare diseases (26/124, 21%). Major reasons for expiry included irrational prescription, inaccurate forecasts, overstocking, dry seasons, and stocking without considering stock-at-hand. Methods of disposal of expired drugs included throwing at pits (74/168, 44.1%); returning drugs to suppliers (51/168, 30.4%); and incineration (33/168, 19.6%). Factors associated with acceptable levels of expiry included the caretaker being female [adjusted OR = 2.9, 95% CI = 1.22–5.08]; having a procurement policy [adjusted OR = 3.9, 95% CI = 1.29–4.81] and practicing first expiry, first out [adjusted OR = 6.07, 95% CI = 4.71–8.70]. Conclusions Veterinary drug expiries are common in Uganda, and environmentally unfriendly methods of disposal are widely used. Acquisition and use of inventory tracking technologies that support First-Expiry-First-Out principles as well as proper disposal of expired medicines are recommended.